GIARDIASIS AND CRYPTOSPORIDIOSIS IN DOGS OF THE WESTERN AREA OF METROPOLITAN LIMA - Sotelo P., Hernán (2013)
The aim of this study was to determine the prevalence of Giardia spp and Cryptosporidium spp in dogs reared in the western districts of Metropolitan Lima and the association with sex, type of diet, stools physical aspect and staying at home. For this, 300 fecal samples were collected from apparently healthy dogs of both sexes and various breeds between 1 month and 12 years of age. The spontaneous sedimentation technique was used for the diagnostics of Giardia spp and the Ziehl-Neelsen modified was used for Cryptosporidium spp. The prevalence was 16.7 ± 4 and 29.7 ± 5.0% for Giardia spp and Cryptosporidium spp respectively. Younger animals showed higher prevalence of Giardia spp (p<0.05) whereas dogs older than 6 years showed higher prevalence of Cryptosporidium spp (p<0.05). Also, Giardia spp was most commonly found in watery stools than in normal feces (p<0.05). None significant differences due to the presence of these protozoa were found in relation to sex, type of diet and staying at home. The results showed the presence of moderate prevalence of Giardia spp and Cryptosporidium spp in canine population of a major urban area of Lima. These dogs could be a serious problem for public health, especially children and immunosuppressed people.